Psychosocial Hazards in the Workplace as an Aspect of Horizontal Segregation in the Nursing Profession - Kowalczuk, Krystyna; Krajewska-Kułak, Elzbieta; Sobolewski, Marek (Frontiers in Psychology, 2018)
Aim: To assess the influence of the psychosocial hazards on the presence of men in the nursing profession. The article refers to the topic of particularly low representation of men among nursing staff in Poland, comparing to what similar statistics show for other countries. The aim of the study was to assess whether the psychosocial hazards in the nursing profession constitute a significant cause of the small number of men in this occupation. Psychosocial hazards are considered here as all the aspects of management and work organization that may negatively affect the employee's mental and physical health. The research was conducted from September 2017 to April 2018 in the Podlaskie Voivodeship (Poland). A total of 640 respondents working as nurses in inpatient health care facilities, including 87% of women and 13% of men, were included in the study. A standardized Work Design Questionnaire for an objective assessment of work stressfulness was used as a research tool. The research has been run by a group of experts, who explained the aim and the meaning of the particular questions to the surveyed group. Afterwards, based on the answers and observations of the responders, the experts filled in the questionnaire. The results of the study show that in almost all the evaluated aspects, the nursing profession was assessed more negatively by surveyed men than women. The most negative aspects reported by women included hazards (a score of 60), complexity (58.3), and haste (50), while those reported by men included haste (70), complexity (66.7), and hazards (65.0). As a conclusion it has been noticed, that results received from the research confirm that psychosocial hazards may have significant impact on the presence of men in the nursing profession in Poland. This study suggests also that the greater psychosocial hazards experienced by male nurses in the workplace, may be in point of fact an effect of particularly low representation of men among practicing nursing staff.